2006
DOI: 10.1590/s0004-282x2006000100013
|View full text |Cite
|
Sign up to set email alerts
|

Expression of p53, Ki-67 and c-erb B2 in growth hormone-and/or prolactin-secreting pituitary adenomas

Abstract: -The subcellular events implicated on the formation and behavior of pituitary adenomas are not fully understood. In this study we investigated the presence of p53, Ki-67 and c-erb B2 in 38 pituitary adenomas with immunohistochemical positivity for GH and prolactin (n=26; 68.4%), for prolactin (n=9; 23.7%) and for GH (n=3. 7.8%). The analyses revealed the following results: 24 (63.2%) tumors expressed variable positivity for c-erb B2, 11 (28.9%) expressed p53 positivity and 11 (28.9%) tumors were variably posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 20 publications
2
19
0
Order By: Relevance
“…The presence of p53 mutations in pituitary tumors is rarely described (28), but some authors found a relationship with proliferative states (29,30). In our patient we detected positivity in 10% of the tumoral cells.…”
Section: Discussionsupporting
confidence: 52%
“…The presence of p53 mutations in pituitary tumors is rarely described (28), but some authors found a relationship with proliferative states (29,30). In our patient we detected positivity in 10% of the tumoral cells.…”
Section: Discussionsupporting
confidence: 52%
“…Other studies have counted randomly selected areas [27] or used a method including 3 areas of the tumor with an even distribution of labeled cells [25]. Some studies have used only a small piece of the biopsy included in tissue microarrays [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…Invasive adenomas can infiltrate the bone and rarely the brain (8). There is no parameter for treatment options and behavior pattern of this type of invasive pituitary adenoma.…”
Section: Discussionmentioning
confidence: 99%